Impact of ABCB1, ABCG2, and CYP3A5 polymorphisms on plasma trough concentrations of apixaban in Japanese patients with atrial fibrillation - Ueshima, Satoshi; Hira, Daiki; Fujii, Ryo; Kimura, Yuuma; Tomitsuka, Chiho; Yamane, Takuya; Tabuchi, Yohei; Ozawa, Tomoya; Itoh, Hideki; Horie, Minoru; Terada, Tomohiro; Katsura, Toshiya (Pharmacogenetics and genomics, 2017)
During anticoagulant therapy, major bleeding is one of the most severe adverse effects. This study aimed to evaluate the relationships between ABCB1, ABCG2, and CYP3A5 polymorphisms and plasma trough concentrations of apixaban, a direct inhibitor of coagulation factor X. A total of 70 plasma concentrations of apixaban from 44 Japanese patients with atrial fibrillation were analyzed. In these analyses, the plasma trough concentration/dose (C/D) ratio of apixaban was used as a pharmacokinetic index and all data were stratified according to the presence of ABCB1 (ABCB1 1236C>T, 2677G>T/A, and 3435C>T), ABCG2 (ABCG2 421C>A), and CYP3A5 (CYP3A5*3) polymorphisms. Influences of various clinical laboratory parameters (age, serum creatinine, estimated glomerular filtration rate, aspartate amino transferase, and alanine amino transferase) on the plasma trough C/D ratio of apixaban were included in analyses. Although no ABCB1 polymorphisms affected the plasma trough C/D ratio of apixaban, the plasma trough C/D ratio of apixaban was significantly higher in patients with the ABCG2 421A/A genotype than in patients with the ABCG2 421C/C genotype (P<0.01). The plasma trough C/D ratio of apixaban in patients with CYP3A5*1/*3 or *3/*3 genotypes was also significantly higher than that in patients with the CYP3A5*1/*1 genotype (P<0.05). Furthermore, the plasma trough C/D ratio of apixaban decreased with increased estimated glomerular filtration rate. These results indicate that ABCG2 421A/A and CYP3A5*3 genotypes and renal function are considered potential factors affecting trough concentrations of apixaban.